King Leopold's Ghost - "Hochschild, Adam." (Boston)
Includes bibliographical references (p. 338-350) and index. CONGO (DEMOCRATIC REPUBLIC) -- RACE RELATIONS --
Keywords: HUMAN RIGHTS MOVEMENTS -- HISTORY -- 19TH CENTURY.;HUMAN RIGHTS MOVEMENTS -- HISTORY -- 20TH CENTURY.;CONGO (DEMOCRATIC REPUBLIC ) - POLITICS AND GOVERNMENT - 1885 - 1908;CONGO (DEMOCRATIC REPUBLIC ) - POLITICS AND GOVERNMENT;FORCED LABOR - CONGO(DEMOCRATIC REPUBLIC) - HISTORY - 20TH CENTURY;FORCED LABOR - CONGO(DEMOCRATIC REPUBLIC) - HISTORY - 19TH CENTURY;INDIGENOUS PEOPLES - CONGO(DEMOCRATIC REPUBLIC) - HISTORY - 20TH CENTURY;INDIGENOUS PEOPLES - CONGO(DEMOCRATIC REPUBLIC) - HISTORY - 19TH CENTURY;CONGO (DEMOCRATIC REPUBLIC ) - RACE RELATIONS - HISTORY - 19TH CENTURY;CONGO (DEMOCRATIC REPUBLIC ) - RACE RELATIONS - HISTORY - 20TH CENTURY